The effect of potentized histamine on serum cortisol - Ward, Adam A. (British Homeopathic Journal, 1995)
The results of a pilot study to assess the effect of potentized histamine on serum cortisol levels in healthy volunteers suggest that there may be a subgroup of people who are particularly sensitive to potentized histamine. It is suggested that a larger double-blind study would provide a useful and easily reproducible way of evaluating the effect of potentized histamine on serum cortisol in vivo using standard laboratory investigations.
Keywords: Potencies; Histamine; Serum cortisol; In vivo